Reasons and intentions in law and practical agency / edited by George Pavlakos, Veronica Rodriguez-Blanco. - Pavlakos, George; Rodriguez-Blanco, Veronica (Cambridge University Press, 2015)
This collection of new essays explores in depth how and why we act when we follow practical standards, particularly in connection with the authority of legal texts and lawmakers. The essays focus on the interplay of intentions and practical reasons, engaging incisive arguments to demonstrate both the close connection between them, and the inadequacy of accounts that downplay this important link. Their wide-ranging discussion includes topics such as legal interpretation, the paradox of intention, the relation between moral and legal obligation, and legal realism. The volume will appeal to scholars and students of legal philosophy, moral philosophy, law, social science, cognitive psychology, and philosophy of action.